Labrador, aerial view of coastline between Kangalaksiorvik Fjord and Nachvak Fjord - Forbes, Alexander, 1882-1965 (1931)
(Series 6) Similar to Series 5, but flight a little further inland. Inshore east coast flight from Nachvak to Kangalaksiorvik. Camera facing right front to line of flight. Grayscale